The global research on meiofauna associated to seagrasses: a bibliometric network analysis - Cocozza di Montanara, Adele; Sandulli, Roberto (Ecological Questions, 2023)
To better understand the state of the art of the research on meiofauna (small metazoan between 500 and 30μm) and seagrasses, a bibliometric network analysis was performed exploring the period from 1981 to 2021 from the Scopus database. The indexed global scientific literature on this topic was explored using VOSviewer software, which allowed us to obtain a comprehensive overview on these topics. A total of 101 publications were identified, revealing that scientific research on meiofauna related to seagrasses is still relatively limited. Results showed that the scientific documents were published by 15 countries, leaded by Australia, Italy, and USA, 50 researchers, and only 7 journals (with a maximum of 8 documents each). De Troch was the most productive author with 14 published documents. Following the most common keywords (meiofauna, seagrass, nematode, and copepoda), “community structure” occurred 25 times, suggesting that the main research field linked to meiofauna and seagrasses is community ecology. The analysis of co-authorship (among researchers and countries), the co-occurrence of keywords and cited journals showed an increasing attention to this topic worldwide and over time. Indeed, although meiofauna is still relatively poorly studied, the awareness of its crucial role in key coastal habitats, such as seagrass beds, is growing.